Quality of Life of Post-Thyroidectomy Patients Before and After the Radioactive Iodine Ablation Therapy: A Quasi-Experimental Study (Journal of Preventive and Social Medicine, 2026)
Background: Postoperative radioactive iodine (RAI) ablation is used in thyroid cancer patients to eliminate residual malignant tissue to reduce recurrence risk and improve quality of life (QoL). This study aimed to evaluate the changes in QoL among thyroid cancer patients before and after RAI therapy following thyroidectomy.Methods: A quasi-experimental study was conducted from August 2022 to July 2025, including 218 thyroid cancer patients post thyroidectomy at Institute of Nuclear Medicine, Dhaka. Data were collected through face-to-face interview using a validated, pre-tested, semi-structured questionnaire at one and three months after surgery (pre-RAI and post-RAI), during which QoL was assessed using the FACT-G scale. Informed consent was obtained from all participant addressing proper ethical issues.Results: The study demonstrated a predominance of female participants (64.2%), with a mean age of 44.14 ± 15.41 years; approximately half of the respondents were aged below 40 years. The majority had attained education up to the SSC level (37.6%), was married (72.9%), and belonged to lower-income groups (74.3%), with housewives comprising the largest occupational category (34.9%). Males had slightly higher median QoL scores than females (97 vs. 96; p